ANTI-PROLIFERATIVE ACTIVITY OF ZIZYPHUS SPINA CHRISTI LEAVES METHANOL EXTRACT AGAINST RHABDOMYOSARCOMA (RD) CELL LINE - Abu-raghif, Ahmed R.; Jasim, Ghaith A.; Hanoon, Muneer M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The aim of this study was to investigate the capability of Zizyphus spina christi methanol extract to inhibit cancer cell line proliferation. Methods: The leaves of Zizyphus spina christi were extracted by cold maceration method. The anti-proliferative activity of the methanol extract against rhabdomyosarcoma (RD) cell line was tested by 3-(4, 5 Dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The phytochemical constituents were identified by gas chromatography-mass spectrometry (GC-MS) analysis. The antioxidant activity was assessed by measuring free radical scavenging activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Results: The percentage extraction yield for leaves with methanol was 20.64%. The methanol extract showed dose dependent inhibition of RD cell line, the IC50 was 154.44 Âµg/ml. GC-MS showed the presence of flavonoid fraction and other compounds with antioxidant activity. The methanol extract demonstrated DPPH scavenging activity with IC50 of 33.91 mg/ml. Conclusion: Methanol extract showed potential anti-proliferative activity against RD cell line, which could be due to its antioxidant activity.